Pericytes for Therapeutic Approaches to Ischemic Stroke - Cao, Lu; Zhou, Yanbo; Chen, Mengguang; Li, Li; Zhang, Wei (Frontiers in Neuroscience, 2021)
Pericytes are perivascular multipotent cells located on capillaries. Although pericytes are discovered in the nineteenth century, recent studies have found that pericytes play an important role in maintaining the blood—brain barrier (BBB) and regulating the neurovascular system. In the neurovascular unit, pericytes perform their functions by coordinating the crosstalk between endothelial, glial, and neuronal cells. Dysfunction of pericytes can lead to a variety of diseases, including stroke and other neurological disorders. Recent studies have suggested that pericytes can serve as a therapeutic target in ischemic stroke. In this review, we first summarize the biology and functions of pericytes in the central nervous system. Then, we focus on the role of dysfunctional pericytes in the pathogenesis of ischemic stroke. Finally, we discuss new therapies for ischemic stroke based on targeting pericytes.